Creative Reading, or the New Life of Literary Works: American Instances - Bruyère, Claire (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2012)
The “creative reading” referred to here is an extension of the reading of literature. To be inspired by a previous text is as old as literature itself; what we wish to understand is why the (re)reading of a number of works of imagination published in the United States between 1915 and 1940 leads contemporary writers, stage or film directors, composers, illustrators, and multi-media artists to adapt or transpose them. Why these works, in particular? Some “creative readers” reveal, in their productions, scripts, projects, and interviews, the ways in which they interpret works by “classic authors” such as Theodore Dreiser, Edgar Lee Masters, Sherwood Anderson, Sinclair Lewis, and Francis Scott Fitzgerald. They also reveal how they hope to bring their spectators or readers, especially the younger ones, to share their enthusiasm and read the source texts. The role of new technology cannot be overestimated, both in artistic creation and in the circulation of information.